Gambaran Kematangan Karir pada Wirausaha (Entrepreneur) Muda - Bayu, Bondan; Widyarini, Nurlaela; Nur’aini, Siti (Jurnal Psikologi, 2024)
Entrepreneurship is one thing that determines the progress and decline of the economy, because in the field of entrepreneurship (entreupreneur) you have the freedom to work and be independent. Career maturity is the level an individual has when mastering career development tasks, both knowledge components and attitudes that are appropriate to the stage of career development. This research uses a descriptive quantitative approach. The subjects in this research were 84 entrepreneurs (en-treupreneurs) in Gumukmas District, Jember Regency who were members of the Gumukmas Young Entrepreneurs (PMG) organization using random sampling. Measurement of career maturity uses an adaptation of the Career Maturity Inventory with 21 items. The overall research results show that the career maturity of entrepreneurs (entreupreneurs) is in the high category at 74%, where entrepreneurs (entreupreneurs) tend to have high career maturity so that young entrepreneurs are ready to face career development tasks such as choosing and making career decisions.